A STUDY ON IMPACT OF BEHAVIOURAL FINANCE ON INVESTMENT DECISION OF SINGLE PARENTS IN SOUTH ASIAN COUNTRIES - Sendilvelu, Kannadas; Shah, Manita Deepak (International Journal of Accounting & Finance Review, 2021)
The purpose of this study is to find out the possible impact of behavioural finance on the investment decision of a single parent. As being an earning/working single parent who usually does not have other possible sources in their family, the decision which they take must be a reliable one and cannot afford to get a second chance. In the study, this study is also one of an effort to assess the impact of behavioural biases in the investment decision-making of a single parent. A questionnaire is designed and responses are collected from 203 respondents who prefer to invest where the level of risk is either low or moderate and are more concerned about losses in their investment than substantial gain. Also, most of the respondents were investing in order to meet some specific purpose, for their retirement plan as well as to educate their children. This study concludes by stating that investors’ risk-taking capacity is dependent on their level of income and the sources of income. Although every Individual is subject to some biases, they tend to think more rational way than an average investor in many ways as they know about their requirements and the investment they make. JEL Classification Codes: G40, G41.